Pendidikan Kesehatan Tentang Pembentukan Kader Rapid Untuk Meningkatkan Derajat Kesehatan Ibu Hamil di Desa Watukosek - Aprilya Tunggo Dewi; Ety Diana Sulistyawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
This community service activity is carried out to optimize community involvement in "RAPID" cadres in an effort to improve the health status of pregnant women, this effort is also expected to form pregnant women health cadres who are integrated with other cadres to support improving the health status of the community as a whole both from the family environment as well as the wider community. The purpose of this activity is to form cadres to increase knowledge, provide assistance to cadres of pregnant women related to the health of pregnant women which will ultimately increase the degree of public health.